Appropriateness of Brain Magnetic Resonance Imaging (MRI) Prescriptions and Imposed Financial Burden: Evidence from Iran - Mohammadreza Kalantarhormozi; Ahmad Yazdanpanah; Mohammadreza Yazdankhahfard; Batool Amiri; Reza Nemati; Milad Sohrabi Shekafti; Hedayat Salari; Atefe Esfandiari (Shahid Sadoughi University of Medical Sciences, 2022)
Background: The use of advanced and expensive technologies requires financial, human and capital resources. Brain Magnetic Resonance Imaging (MRI) has high contrast sensitivity for visualizing differences among the tissues. Unnecessary diagnostic imaging imposes excessive cost on health systems. This study aimed to determine the appropriateness of brain MRI prescriptions in 2021. Methods: This cross-sectional study recruited 274 patients who referred to Bushehr teaching hospital. They had been prescribed MRI of the brain due to headache and dizziness. We used the data collection form developed in the previous study. The appropriateness of the brain MRI prescription was determined based on the appropriate indications during 2021. Results: About 61 % of the referrals were due to headache and 39 % were because of dizziness. Overall, MRI was evaluated as inappropriate for about 38 % of the patients. The appropriateness of prescriptions had a significant relationship with age, gender, education, job status, complaint, prescribing physician, and MRI applicant with P-value > 0.050. Conclusion: Findings revealed more than one-third of brain MRI services were not clinically appropriate. Due to the high cost of MRI, it is necessary to make prescriptions in accordance with indications to prevent unnecessary diagnostic procedures and to prevent induced demand. Health system policymakers and healthcare providers should develop clinical guidelines and implement them to reduce the costs of health systems.